The Effect of Training and Work Discipline on Employee Work Productivity at Pt Surya Toto Indonesia - Riyan Setiawan; Azimah Hanifah (Dinasti Publisher, 2025)
This study aims to examine and analyze the influence of training and work discipline on work productivity.The method in collecting data in this study was conducted by distributing questionnaires to 89 employees of PT. Surya Toto Indonesia. The research method used is quantitative method which is associative by using primary data.The result of study indicate that training has a positive and significant effect on work productivity with t count values of 3.053 > 1.98 and significant 0,003 < 0,05, work discipline has a positive and significant effect on work productivity with a value of t count of 3.466 > 1.98 and significant 0,001 < 0,05. Together training and work discipline have a positive and significant effect on work productivity with an F value of 24.997 > 3.10 and a significant value 0,000 < 0,05.